2015
DOI: 10.9734/ajaees/2015/8975
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influences Consumption of Processed Sweet Potato Products in Tanzania

Abstract: The general objective of this study was to describe a socioeconomic factor that influences consumption of processed sweet potato products in the study area. The study was cross sectional in design and was conducted in Shinyanga and Mwanza regions. The study employed individual interviews, focused group discussions, review of relevant practical documents and discussions from a total of 30 surveyed households. The data collected was summarized using Statistical Package of Social Science (SPSS) windows versions 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(2 reference statements)
0
0
0
Order By: Relevance
“…It was observed that farmers' dominance in SPP is slightly skewed towards female. The slightly dominance of female over male is similar to the findings of Mmasa (2014); he found relatively more dominance of female in SPP. The dominance of female over male may be partly due to the fact that SP is considered as a minor crop as it does not command a place over cassava, yam or plantain in the market, hence, most males are not farming SP.…”
Section: Discussionsupporting
confidence: 77%
“…It was observed that farmers' dominance in SPP is slightly skewed towards female. The slightly dominance of female over male is similar to the findings of Mmasa (2014); he found relatively more dominance of female in SPP. The dominance of female over male may be partly due to the fact that SP is considered as a minor crop as it does not command a place over cassava, yam or plantain in the market, hence, most males are not farming SP.…”
Section: Discussionsupporting
confidence: 77%